2014
DOI: 10.1177/1464420714525542
|View full text |Cite
|
Sign up to set email alerts
|

Fractographic analysis of compression failures in unidirectional carbon fiber reinforced plastic composites

Abstract: Resin infusion process with/without the application of external pressure was employed for fabrication of unidirectional carbon fiber reinforced plastic composites. The prepared samples were tested under compression loads. Three kinds of fracture modes, viz., in-plane shear, complex fracture and through-thickness shear fractures were noticed. It was observed that samples fabricated with application of pressure exhibited in-plane and complex fracture modes whereas other samples displayed through-thickness fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In microstructural studies, SEM images are utilized to visualize the random orientation of fibers, which leads to anisotropic behavior, increasing voids/declining interfacial bonding as laminate thickness grows, and anisotropic behavior. Kumar et al 78 described fractographic features in tensile‐failed aerospace composites. In this study, tension testing was performed on composite specimens made of unidirectional glass and unidirectional carbon fiber‐reinforced plastic.…”
Section: Fractography Of Frp Laminate Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…In microstructural studies, SEM images are utilized to visualize the random orientation of fibers, which leads to anisotropic behavior, increasing voids/declining interfacial bonding as laminate thickness grows, and anisotropic behavior. Kumar et al 78 described fractographic features in tensile‐failed aerospace composites. In this study, tension testing was performed on composite specimens made of unidirectional glass and unidirectional carbon fiber‐reinforced plastic.…”
Section: Fractography Of Frp Laminate Compositesmentioning
confidence: 99%
“…In compressive failures of fiber‐reinforced polymer composites, three main damage mechanisms were identified: microcracking, crack bridging, and fiber microbuckling resulting in kink‐band formation. Kumar et al 78 investigated three types of fracture modes on CFRP samples: in‐plane shear, complex fracture, and through‐thickness shear fractures under compression load test. A detailed fractographic examination revealed that microbuckling of individual fibers caused in‐plane and through‐thickness shear fractures; complicated failure is caused by longitudinal splitting followed by microbuckling.…”
Section: Fractography Of Frp Laminate Compositesmentioning
confidence: 99%
“…The deformation and fracture of unidirectional FRP composites under compressive load are affected by factors such as the fiber modulus, initial arrangement of fibers, internal defects, and fiber-matrix interface, resulting in changes in the compressive behavior and failure mechanism. [15][16][17][18][19][20] In general, the axial compressive failure modes of unidirectional FRP composites are debonding, resin fracture, fiber buckling instability, kinking, and fiber crushing. In the case of a good interface property and fewer defects, the fiber in the composite first reaches the critical instability state, followed by fiber buckling or microbuckling.…”
Section: Introductionmentioning
confidence: 99%